Endodontic Management of a Maxillary First Molar with a Separated Instrument and a Second Mesiobuccal Canal (MB2): A Case Report - Sirisak, Wannee (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This report presents a case study of root canal treatment in an 18-year-old Thai female diagnosed with irreversible pulpitis with symptomatic apical periodontitis in the maxillary left first molar (#26). The treatment was complicated by the presence of a fourth canal (MB2 canal) and a separated instrument located in the middle third of the mesiobuccal (MB) canal. A staging platform technique combined with ultrasonic tips was employed to manage the separated instrument. The decision was made to discontinue retrieval efforts when the risk of root perforation became significant. The canal was subsequently cleaned, shaped, and obturated up to the level of the separated instrument. The previously undetected MB2 canal was located and treated during the procedure. The patient remained asymptomatic during the 6-month follow-up period, and radiographic evaluation showed no signs of additional periapical pathology, indicating a successful outcome. This case highlights the importance of appropriate treatment planning, sound clinical decision-making, and effective infection control in achieving successful root canal treatment, even in anatomically complex cases with procedural complications such as instrument separation.